Between Flexibility and Firmness: Imam al-Hishni's Fiqh Methodology in Responding to Contemporary Islamic Economic Dilemmas - Yaqeen Faiz; Muhamad Padli; Pathur Rahman; Ahmad Riki; Syarif bin Muhammad Romli Samae (NALAR FIQH: Jurnal Hukum Islam, 2025)
The digital economic transformation has propelled Islamic financial transactions to reach USD 3.95 trillion in 2023; however, an epistemological discontinuity persists between contemporary muamalah practices and classical Islamic intellectual heritage. This research analyzes the jurisprudential choices (ikhtiyarat fiqhiyyah) of Imam Taqiyuddin al-Hishni (752-829 AH) concerning commercial transactions involving discerning minors (mumayyiz) and the sale of musical instruments, while exploring his istinbath methodology and its relevance to contemporary Islamic economic issues, particularly within the contexts of e-commerce and Indonesia's halal creative industry valued at USD 7.2 billion.Employing a qualitative approach with descriptive-analytical library research, this study utilizes primary sources including al-Hishni's Kifayah al-Akhyar and classical biographical works, supplemented by secondary sources encompassing exegetical literature and comparative fiqh. Data analysis applies directed content analysis techniques grounded in the theoretical framework of usul fiqh and maqasid al-shariah.Research findings demonstrate that al-Hishni implemented contextual flexibility regarding transactions by discerning minors, permitting such transactions when guardian consent and equivalent value exist, based on the principles of 'ammah bihi al-balwa and istishlah. Conversely, he adopted a stringent position prohibiting the trade of musical instruments by applying sadd al-dzari'ah, arguing that their primary function induces heedlessness from the remembrance of Allah despite their economic value.Al-Hishni's methodology, which distinguishes when to exercise flexibility in technical-procedural matters for public interest and when to maintain firmness in protecting spiritual values, offers significant theoretical contributions to the development of the theory of ahliyyah al-ada' al-naqishah (incomplete legal capacity to act) in Islamic economic law. Furthermore, it provides practical contributions as a reference framework for formulating DSN-MUI fatwas regarding youth participation in Islamic fintech platforms and developing comprehensive halal entertainment certification standards for Indonesia's creative industry ecosystem.